Formulation Development and Evaluation of Transdermal Patches of Diclofenac sodium as a Analgesics - Dr. Ehtesham Ansari,; Nikita Pagar,; Rekha Bornare,; Shweta Bhagwat,; Dr. Rasika Bhalke, (Asian Journal of Pharmaceutical Research and Development, 2026)
Diclofenac is commonly prescribed for the treatment of pain, inflammation, and arthritic disorders. However, oral administration of diclofenac may lead to gastrointestinal side effects and extensive first-pass metabolism, which can reduce its therapeutic effectiveness. Transdermal drug delivery systems (TDDS) provide an alternative method of administration by delivering the drug through the skin in a controlled manner. This research describes the formulation and evaluation of diclofenac transdermal patches prepared using different polymers, plasticizers, and permeation enhancers. Various preparation techniques, including solvent casting and solvent evaporation methods, are discussed. The review also summarizes important evaluation tests such as thickness, weight uniformity, folding endurance, drug content analysis, surface pH . In addition, the influence of permeation enhancers and release kinetics on drug delivery performance is highlighted. Diclofenac transdermal patches have shown significant potential in improving patient compliance, reducing gastrointestinal complications, and providing sustained drug release. Hence, TDDS can be considered a suitable and promising approach for effective management of pain and inflammatory conditions.